Incidence of anemia in pregnancies of 14 to 18 years in the maternity area of the hospital Martin Icaza de Babahoyo - Loqui Sánchez, Teresa Magaly (Revista Universidad de Guayaquil, 2017)
It was established as a general objective for this research, know the incidence of anemia in pregnant women from 14 to 18 years in the Maternity Hospital Babahoyo Martin Icaza. It requires assessing erythrocyte indices obtained by referring to the study objects issued by the hospital, in turn, a comparison is made of the same medical history. The results were analyzed in percentage terms, comparing various factors within the red cell indices as hemoglobin, hematocrit, Mean Corpuscular Volume, MCHC and ADE, in turn grouped by age group in relation to the low percentage values for each index. It is demonstrated by results that a high percentage of pregnant teenagers in the city of Babahoyo suffer from eating problems that have led to the development of anemia in the study objects, a problem that affects a greater percentage of adolescents between 16 and 17 years. The proposal to develop aims to promote proper nutrition through detailed educational information within a nutritional plan, thus minimizing the high rates of the disease obtained.